Sequencing and analysis of the complete mitochondrial genome of Crocidura tanakae from China and its phylogenetic analysis - Zhi-Min, Jin (Mitochondrial DNA B Resour, 2019)
The complete mitogenome sequence of Crocidura tanakae was determined using long PCR. The genome was 16,969 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, 1 origin of L strand replication and 1 control region. The overall base composition of the heavy strand is A (32.5%), C (22.3%), T (31.9%), and G (13.3%). The base compositions present clearly the A–T skew, which is most obviously in the control region and protein-coding genes. Mitochondrial genome analyses based on MP, ML, NJ, and Bayesian analyses yielded identical phylogenetic trees. The five Crocidura species formed a monophyletic group with the high bootstrap value (100%) in all examinations. This study verifies the evolutionary status of C. tanakae in Soricidae at the molecular level. The mitochondrial genome would be a significant supplement for the C. tanakae genetic background.